Pregnancy detection in reindeer (Rangifer tarandus tarandus) : comparison of transrectal ultrasound, abdominal palpation and herders' visual cues in late gestation - Paul, Elisabeth (SLU/Dept. of Animal Nutrition and Management (until 231231), 2014)
Pregnancy detection during late gestation (last trimester) in domesticated reindeer (Rangifer tarandus tarandus) gives the possibility to select and enclose the pregnant reindeer during calving as protection against predation. The aim of the present study was to compare transrectal ultrasonography and palpation, and also to describe visual examination as traditionally used by herders as pregnancy detection methods in reindeer.